2012
DOI: 10.1111/j.1445-5994.2011.02440.x
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners' knowledge and management of viral hepatitis in the migrant population

Abstract: There were gaps in the knowledge of GPs particularly concerning natural history, diagnosis, treatment availability and management of pregnant or lactating women with viral hepatitis. Specific educational initiatives targeting these deficits are required as well as increased availability of language resources for managing patients from a non-English-speaking background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 16 publications
7
23
0
Order By: Relevance
“…Majority of the respondents agreed that Hb< 8 and TLC/Platelets around 2500-40,000 is marker for reduction of anti-HCV therapy. Similar findings were reported in a study conducted in Australia where majority of the practitioners were well aware of the screening tests required for chronic hepatitis [8]. The results of the study highlighted that half of the respondents agreed that pregnant and lactating women, low Hb cases and patients with uncontrolled diabetes require observation but not treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Majority of the respondents agreed that Hb< 8 and TLC/Platelets around 2500-40,000 is marker for reduction of anti-HCV therapy. Similar findings were reported in a study conducted in Australia where majority of the practitioners were well aware of the screening tests required for chronic hepatitis [8]. The results of the study highlighted that half of the respondents agreed that pregnant and lactating women, low Hb cases and patients with uncontrolled diabetes require observation but not treatment.…”
Section: Discussionsupporting
confidence: 75%
“…16,19 Educating people with CHB was identified by Australian GPs as an important responsibility in their clinical management 20 although systemic barriers have been identified in providing this support, given GPs' busy schedules and workloads, 21,22 and hepatitis B knowledge gaps among some GPs. 21,23 A study from one tertiary hospital liver clinic reported that clinicians did not provide detailed information about hepatitis B during most ongoing monitoring consultations. 12 This study suggested that even if people with CHB were provided with detailed information upon diagnosis, ongoing education is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 GPs' guideline awareness and professional development were associated with increased screening in the US and Australia; [33][34][35] language difficulties have been identified as barriers to testing and treatment. 34,36 In the UK, new entrant migrants identified non-migrant-friendly …”
mentioning
confidence: 99%